2009
DOI: 10.1097/bsd.0b013e318167b0a6
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Deformity in Patients With Sotos Syndrome (Cerebral Gigantism)

Abstract: The development of spinal deformity is a common finding in children with Sotos syndrome and in our series it occurred in adolescence in 4 out of 5 patients. There is significant variability on the pattern of spine deformity, ranging from a scoliosis through kyphoscoliosis to a pure kyphosis, and also the age at presentation and need for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Scoliosis is recognized to be a common symptom associated with Sotos syndrome, with Sotos et al reporting a case with mild scoliosis in their original series of five patients 16 and confirming the association in a later report 12–16 . Although the causes or factors that predispose Sotos syndrome patients to scoliosis remain unknown, scoliosis has been observed in approximately one-third of patients with variable severity 1 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Scoliosis is recognized to be a common symptom associated with Sotos syndrome, with Sotos et al reporting a case with mild scoliosis in their original series of five patients 16 and confirming the association in a later report 12–16 . Although the causes or factors that predispose Sotos syndrome patients to scoliosis remain unknown, scoliosis has been observed in approximately one-third of patients with variable severity 1 .…”
Section: Discussionmentioning
confidence: 94%
“…1 Scoliosis is recognized to be a common symptom associated with Sotos syndrome, with Sotos et al reporting a case with mild scoliosis in their original series of five patients 16 and confirming the association in a later report. [12][13][14][15][16] Although the causes or factors that predispose Sotos syndrome patients to scoliosis remain unknown, scoliosis has been observed in approximately one-third of patients with variable severity. 1 Examination into the genetic background of the 25 scoliosis patients with NSD1 aberrations in this study revealed that the 20 patients with microdeletions had more prominent and progressive scoliosis compared to the five patients with mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of our patients underwent surgical treatment. In the literature there are reports where majority of patients did not require surgery [8][9][10]; however Tsirikos et al [4] recently reported five patients with Sotos syndrome that required surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The disorder is associated with developmental delay, hypotonia, joint hyperextensibility and behavioral and learning disturbances often with mild mental retardation. Hypotonia, joint hyperextensibility and excessive growth in childhood are the main features of the syndrome [4][5][6]. The incidence of Sotos syndrome is 1/10,000-1/15,000 live births with an autosomal dominant pattern of inheritance [3].…”
Section: Introductionmentioning
confidence: 99%